The Reorganization of Hispania Citerior under Augustus - López Barja de Quiroga, Pedro (Gerión. Revista de Historia Antigua, 2017)
Provincia Transduriana was a Roman province, not the territory assigned to a legate; Gallaecia et Asturia were never integrated within the provincia Lusitania; the oriental border of the Transduriana probably was located at Noega.
Keywords: Transduriana. Province. Delegated jurisdiction. Provincial Governor. Gallaecia. Bronze from El Bierzo.